Бій за Глухів – міф чи реальність? - Бєлашов, В.І. (Сіверщина в історії України, 2020)
До недавнього часу при вивченні питання визволення міста
Глухова від нацистської окупації дослідники не мали достатньої
кількості документального матеріалу. Його частину у вересні
2019 р. було отримано автором-укладачем цієї публікації з Центрального архіву Міністерства оборони Російської Федерації у
місті Подольську. У статті на основі архівних документів встановлюється картина реальних подій, пов’язаних з визволенням міста Глухова у
кінці серпня 1943 року. The writing of the article was caused by the urgent need to display
on the basis of archival documents the content of the battle for Hlukhiv
at the end of August 1943.
To date, researchers have only worked on selected documents, the
publication of which has not fully covered this important issue. For this
reason, the purpose of writing an article is to fully reflect their content.
At the same time, the author set himself the task of accumulating the
required amount of archival material and its processing by methods
of analysis, synthesis, systematic, comparison
As a result of studying the documents, the sequence and content
of the events were established, for which, first of all, the reports
on the fighting of the 23rd Panzer Brigade were used, including its
reconnaissance of the beginning of the battle for Hlukhiv in the morning
of 30.08.1943, and the log of the 9th the tank corps, the pages of
which reveal the true cause that led to the two stages of the battle.
It consisted of a mismatch between the commander of the 60th Army
and the commander of the 9th Panzer Corps, who, without knowing
the first, made the decision to launch actions aimed at Hlukhiv’s
liberation, initially only by the forces of the 28th Reconnaissance
Battalion with the auxiliary units. These small forces took Hlukhiv
to 13-00. This victory did not give rise to the Radinformbureau’s
announcement of Hlukhiv’s release on August 30, 1943, although the
main forces of the 23rd Panzer Brigade broke into the city at 4.45pm.
These events are part of the f irst phase of hostilities.
The events of the second stage of the battle are revealed in
the combat log of the 205th Guards Rif le Regiment of the 70th
Guards Rif le Division, from which it became known that 9.30
p.m. the assault on the north-eastern part of the city began and
by 24-00 its units had completely cleared the city of the enemy.
The historical form of the 70th Guards Rif le Division states that
by 2-00 on 31.08.1943, parts of the division had been completely
conquered by Hlukhiv .
The combat log of the 17th Guards Rifle Corps clearly states that
the 70th Guards Rifle Division occupied Hlukhiv at 2-00 on August
31, 1943, indicating that the day of the city’s liberation should be
considered August 31.
Military memoirs, diaries and audio recordings substantially
supplemented the content of the ev ents of the tw o-stage battle.
The author concludes that the Battle of Hlukhiv at the end of
August 1943 is a real event that initiated the liberation of a number
of Ukrainian cities.